Sustainable Mask Waste Management Strategies for Enhancing Urban Resilience in Denpasar Bali - I. Nengah Muliarta (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The increase in COVID-19 cases also increases waste production, including mask waste. The use of masks is one of the steps to mitigate transmission during the pandemic. Used masks, on the other hand, are a source of environmental pollution and can facilitate the spread of COVID-19. The study was prepared to evaluate efforts to mitigate COVID-19 spread through mask waste management. This study was compiled using observation methods, literature studies and secondary data collection to strengthen the observation results. As a result, the Denpasar City Government has mitigated the spread of COVID-19 through socialization and massive control of health protocols up to the village level. Alternative mitigation measures to curb the spread of COVID-19 through mask waste management have not been implemented, despite the Ministry of Environment and Forestry's circular letter Number SE.3 / MENLHK / PSLB3 / PLB.3 / 3/2021. Mask waste at the household level is still mixed with household waste, and there is no unavailability of used mask shelters in public facility areas. This phenomenon is thought to have contributed to cases of transmission between family members or family clusters, office clusters, school clusters, market clusters, and religious ceremonial clusters Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 15: Life on Land